2011
DOI: 10.15560/7.5.656
|View full text |Cite
|
Sign up to set email alerts
|

Social wasps of Unilavras/Boqueirão Biological Reserve, Ingaí, state of Minas Gerais, Brazil

Abstract: Social wasps (Hymenoptera, Vespidae, Polistinae) usually build nests using vegetable materials mixed with water and salivary secretion, resulting in a product similar to paper. Between April 2009 and March 2010 an inventory of these wasps was made at Unilavras/Boqueirão Biological Reserve, located in the municipality of Ingaí-MG. Thirty four species of social wasps belonging to ten genera were recorded, Polybia fastidiosuscula Saussure (1854) was the most common.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Survey studies on social wasps in São Paulo state, Brazil. Souza et al 2010;Henrique-Simões et al 2011;Souza et al 2011;Tanaka Junior and Noll 2011;Locher 2012), it is observed that the most abundant species in Ubatuba, Agelaia angulata, A. nr. centralis and Angiopolybia pallens were not collected in other studies, with the latter having been observed in another area of Atlantic Forest in Bahia (Santos et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Survey studies on social wasps in São Paulo state, Brazil. Souza et al 2010;Henrique-Simões et al 2011;Souza et al 2011;Tanaka Junior and Noll 2011;Locher 2012), it is observed that the most abundant species in Ubatuba, Agelaia angulata, A. nr. centralis and Angiopolybia pallens were not collected in other studies, with the latter having been observed in another area of Atlantic Forest in Bahia (Santos et al 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Different authors report an expressive richness of social wasps in areas of Riparian Forest when compared to other ecosystems (Diniz & Kitayama 1994;Clemente 2009;Henrique-SimõeS et al 2011;Pereira & antonialli-Junior 2011;loCHer 2012;bruniSmann et al 2016). The Riparian Forests have a large vegetal complexity which may favor social wasps, as it provides a variety of physical supports to nest foundation, rises the amount and heterogeneity of feeding resources, impose less microclimate variability and rises the density of colonies (lawton 1983;Diniz & Kitayama 1994;Souza et al 2010).…”
Section: Resultsmentioning
confidence: 99%
“…According to Carpenter (2004) twenty five genera of Polistinae are known and twenty one can be found in the Neotropics and the social wasps produce a paper-like substance by mastication of vegetation to build their nests (Gallo et al, 1988). Henrique-Simoes et al (2011) reported the lack of studies of social wasps in several Brazilian ecosystems, which makes it more difficult to understand the distribution and biology of these insects.…”
Section: Introductionmentioning
confidence: 99%